Exploring the Relationship Between Objective Pupillometry Metrics and Midline Shift. Issue 6 (28th December 2021) - Giamarino, Kathryn; Blessing, Robert; Boelter, Christopher; Thompson, Julie A.; Reynolds, Staci S.
ABSTRACT: BACKGROUND: Pupillary examinations provide early subtle signs of worsening intracranial pathology. Objective pupillomtery assessment, although not yet the standard of care, is considered best practice. However, inconsistent findings from objective pupillometry studies have caused a lack of consensus among clinicians; as such, no clinical guidelines are available to guide clinical use of objective pupillometer devices. To add to the body of evidence, the purpose of this project was to explore the relationship between objective pupillometry metrics and midline shift (MLS). METHODS: A retrospective chart review of pupillometer data was conducted. Midline shift was correlated with objective pupillometry metrics including Neurological Pupil Index (NPi), pupil size, and anisocoria. Midline shift was measured for the patient's initial neuroimaging and with any defined neurological change. Spearman ρ was used for statistical analysis of correlations between pupillometer metrics and MLS measured at both the septum pellucidum and pineal gland. RESULTS: A total of 41 patients were included in the analysis; most were White (58.5%) and male (58.5%), with a mean (SD) age of 58.49 (16.92) years. Spearman ρ revealed statistically significant positive correlations between right pupil NPi and anisocoria with MLS, and significant negative correlations between left pupil NPi and pupil size with MLS. CONCLUSIONS: Results from this project are consistent with previous studies. Objective pupillometry continues to be a valuable component of a comprehensive neurological examination, because it has the ability to discern early and subtle changes in a patient's neurological status, leading to lifesaving interventions.